KELAYAKAN MEDIA FLIPBOOK PERILAKU KONSUMSI BUAH MASYARAKAT KOTA PONTIANAK PADA SUBMATERI MENU SEHAT - Winarni, Nurkaida; Cadramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe low frequency of fruit consumption by the community in Pontianak City should be anticipated through education, for example by using a learning media that isÂ designed from the results of research on fruit consumption behavior in the community. This study aimed to determine the feasibility of a flipbook media that contained a study on fruit consumption behavior in Pontianak as a learning media in Sub-Material of healthy food menus for grade XI high schools. The study was conducted in the form of descriptive research with a non-test data collection technique in the form of a questionnaire. The media were validated by experts consisting of two lecturers of the Biology Education Study Program of FKIP UNTAN and three biology teacher in high school Pontianak. The validation result was analyzed using the Content Validity Ratio (CVR). Based on the minimum value of Lawshe CVR for five validators, (CVR = 0,99) the flipbook media was suitable as the learning media on the Sub-Material of Healthy Food Menus for second grade of high school.Â Keywords: Feasibility, Healthy Menu, Flipbook